Personal Inflation Calculator - Trenovski, Borce (Center for Economic Analyses (CEA), 2009)
To avoid imprecision and to adjust the inflation to every individual's consumer basket, we created the personal inflation calculator. This calculator gives the opportunity to every person to calculate their personal inflation rate(adjusted to their consumer basket). The number is always significantly different from the average inflation rate given by the Statistical Office. That was the reason why Center for Economic Analyses made the PersonalInflation Calculator, which is available on the organization's web site. The Personal Inflation Calculator will solve the doubts of the Macedonian citizens about the influence of the inflation over their personal budgets.
Keywords: inflation, personal inflation, calculator